Composition and concentration of suspended matter in the Zhongsha Great Atoll, South China Sea, before and during the summer monsoon - Yan, Wenwen; Du, Jun; Gu, Dongqi; Wang, Yongzhi; Xu, Guoqiang; Wang, Guanxun; Sun, Yonggen; Li, Ping; Chen, Wei (Frontiers in Marine Science, 2024)
Suspended matter in seawater carries abundant nutrients and carbon, playing a significant role in carbon cycle and ecosystem in many oceanic settings such as atolls. The Zhongsha Great Atoll (hereafter ZGA), located in the deep South China Sea, sustains a both regionally and globally important ecosystem. Characteristic of the suspended matter in this area, however, remains poorly investigated. Using a data set encompassing temperature, salinity, depth, and suspended matter concentration (hereafter SMC) of seawater collected respectively in May 2019 (spring-summer monsoon transition period) and June 2020 (summer monsoon outbreak period) in the ZGA, the main components and spatial distribution of suspended matter together with their influencing factors were comprehensively analyzed. Our results show that the components of suspended matter vary widely in space and include more than 20 types of materials such as planktonic remains and biogenic siliceous debris. During the transit between spring and summer monsoons, the SMC in seawater was generally low, with an average value of approximately 3.26 mg L-1, which decreased from the surface to the middle layer and then increased to deep waters; Horizontally, the SMC in the west was generally higher than that in the east likely because the wind-driven current transport significant amounts of particles from the east to the west. During the 2020 summer monsoon outbreak, average SMC in this area was 6.27 mg L-1, higher than that during the 2019 spring-summer monsoon transit. Moreover, significantly higher SMC in the 1-100 m layer and lower SMC in the 150 m layer were observed in the west. Owing to the impact of mesoscale eddies, low SMC in the surface layer and high concentrations in the bottom layer can occur in parts of the ZGA, leading to the deepening of the west-high and east-low distribution layers of SMC during the 2020 summer monsoon outbreak. Notably, we for the first time have observed an anomalously high SMC in the 1–100 m layer of the northwest area during the 2020 summer monsoon outbreak. This anomaly is higher than any previously reported values in the South China Sea and can be attributed to the multiple monsoon impacts. Sources of suspended matter, topography, currents, and wind field were identified as the main factors influencing the spatial distribution of SMC in this area. Our findings provide a basic context for understanding the sources and dynamics of suspended material in atolls.